EP.WE.47Cholecystectomy During COVID-19: A Single Centre Experience. (28th October 2021) - Ghassemi, Nader; Rathod, Sneha; Salgaonkar, Hrishikesh; Nnaji, Martin; Athwal, Tejinderjit; Cheruvu, Chandra
Abstract: Background: The COVID-19 pandemic has significantly impacted healthcare delivery globally with consequent restructuring of surgical services during the peak period and prioritisation of emergency and cancer surgery over elective operations. We present outcomes for laparoscopic cholecystectomy during the peak period for COVID-19 in the UK and compare this with data for the same period in 2019 Methodology: This is a prospectively study. Analysis of collected data on patients who underwent laparoscopic cholecystectomy during the peak period for COVID-19 from 1st March 2020 – 30 th June 2020 (study cohort) at the Royal Stoke University Hospital. Data from the same period in 2019 (control cohort) was compared and analysed. Results: 104 patients underwent a laparoscopic cholecystectomy during the peak period compared to 217 during the same period in 2019. Median age in the study cohort was 51.5 years (15-84 years) and 52 years (19-91 years) in the control cohort (p = 0.49). Male to Female ratio was 1:2 in the study cohort and 1:2.2 in the control cohort (p = 0.67) Emergency admissions constituted the majority of cases and there was no statistically significant difference between both groups (61.5% vs 61.8%, p = 0.49). Most cholecystectomies were for biliary colic (41.3% vs 35.5%) and cholecystitis (37.5% vs 43.8%), and there was no statistically significant difference between both groups (p = 0.31 and p = 0.29 respectively). Conclusion: This study demonstrates that laparoscopic cholecystectomy was feasible and safe in patients with symptomatic gall bladder disease during the peak period for COVID-19 when compared to a historic cohort in 2019.